Characterization of the proteins of bacterial strain isolated from contaminated site involved in heavy metal resistance - a proteomic approach - Bar, Chinmayee; Patil, Rajendra; Doshi, Jignesh; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2007)
The present study describes response of a bacterial strain isolated from a polluted river to heavy metal toxicity. The bacterium was identified to be Klebsiella pneumoniae by biochemical tests using API 20E strips and 16S ribotyping. The isolate was studied for its tolerance to two heavy metals, i.e., cobalt (Co2+) and lead (Pb2+) by growing it in citrate mineral medium (CMM). Proteomic approach involving two-dimensional polyacrylamide gel electrophoresis (2D PAGE) and mass spectrometry (MS) was used to identify the differentially expressed proteins under heavy metal stress. Two of the differentially expressed proteins were identified to be L-isoaspartate protein carboxymethyltransferase type II and DNA gyrase A. To our knowledge, this is for the first time that K pneumoniae has been reported to be present in metal contaminated site and L-isoaspartate protein carboxymethyltransferase type II protein to be over expressed under heavy metal stress. The role of these proteins in metal tolerance is discussed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2D PAGE; heavy metal toxicity; Mass spectrometry

Synthesis of Ag-Pt alloy nanoparticles in aqueous bovine serum albumin foam and their cytocompatibility against human gingival fibroblasts - Singh, A. V.; Patil, R.; Kasture, M. B.; Gade, Wasudeo N.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
Foams of bovine serum albumin (BSA) have been utilized for synthesizing in situ protein capped Ag-Pt alloy nanoparticles. The in vitro cytotoxicity and the rate of proliferation of human gingival fibroblasts (HGFs) in presence of the above synthesized alloy nanoparticles is investigated. Expression profile of protein involved in detoxification, i.e. metallotheonein (MT) were assayed by ELISA and expression of mRNA transcripts by reverse transcription polymerase chain reaction (RT-PCR). Cytotoxicity results suggested that protein capped nano-alloys might be promising candidates for implants and prosthetic material. RT-PCR and ELISA confirmed the expression of MT. in cells treated with the alloy nanoparticles. Morphology variation studied by SEM also confirms that cells treated with alloy nanoparticles present an intact morphology. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alloy nanoparticles; Biocompatibility; ELISA; Human gingival fibroblasts; mRNA; Protein foams

Effects of arsenite stress on growth and proteome of Klebsiella pneumoniae - Daware, Vandana; Kesavan, Suresh K.; Patil, Rajendra; Natu, Arvind; Kumar, Ameeta; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2012)
In the present study an arsenite, As(III), tolerating bacterium, MR4, was isolated from Mulla River Pune, India, capable of reducing arsenate to arsenite and identified as Klebsiella pneumoniae (HQ857583). Comparative proteomic analysis using two-dimensional gel electrophoresis (2-DGE) and matrix assisted laser desorption ionization-time of flight-time of flight (MALDI-TOF/ TOF) was used to monitor the proteins undergoing changes in expression levels under 2.5 mM As(III) stress. The 2-DGE proteome map has shown that 60 proteins were differentially expressed under As(III) stress, of which 39 proteins were successfully identified with a MASCOT score greater than 70 (p < 0.05). Among the identified proteins, membrane transport/ binding proteins, porins, and amino acid metabolism enzymes were down-regulated while stress responsive proteins and antioxidant enzymes were up-regulated. Proteins involved in carbohydrate metabolism, particularly those in pentose phosphate pathway were also up-regulated while those involved in pyruvate metabolism were down-regulated. However, proteins involved in glycolysis and tricarboxylic acid cycle showed a mixed regulation response. These findings provide new insights into the probable mechanisms by which K. pneumoniae (HQ857583) could be adapting to As(III) stress. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: (2-DGE); Arsenite stress; Klebsiella pneumoniae; MALDI-TOF-TOF; Two dimensional gel electrophoresis

Nanowires of silver-polyaniline nanocomposite synthesized via in situ polymerization and its novel functionality as an antibacterial agent - Tamboli, Mohaseen S.; Kulkarni, Milind V.; Patil, Rajendra H.; Gade, Wasudeo N.; Navale, Shalaka C.; Kale, Bharat B. (Colloids and Surfaces B-Biointerfaces, 2012)
Silver-polyaniline (Ag-PANI) nanocomposite was synthesized by in situ polymerization method using ammonium persulfate CAPS) as an oxidizing agent in the presence of dodecylbenzene sulfonic acid (DBSA) and silver nitrate (AgNO3). The as synthesized Ag-PANI nanocomposite was characterized by using different analytical techniques such as UV-visible (UV-vis) and Fourier transform Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), thermo gravimetric analysis (TGA). X-ray diffraction (XRD), and transmission electron microscopy (TEM). UV-visible spectra of the synthesized nanocomposite showed a sharp peak at similar to 420 nm corresponding to the surface plasmon resonance (SPR) of the silver nanoparticles (AgNPs) embedded in the polymer matrix which is overlapped by the polaronic peak of polyaniline appearing at that wavelength. Nanowires of Ag-PANI nanocomposite with diameter 50-70 nm were observed in FE-SEM and TEM. TGA has indicated an enhanced thermal stability of nanocomposite as compared to that of pure polymer. The Ag-PANI nanocomposite has shown an antibacterial activity against model organisms, a gram positive Bacillus subtilis NCIM 6633 in Mueller-Hinton (MH) medium, which is hitherto unattempted. The Ag-PANI nanocomposite with monodispersed AgNPs is considered to have potential applications in sensors, catalysis, batteries and electronic devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Conducting poly(aniline); In situ polymerization; Nanocomposite

Arsenomics of exiguobacterium sp PS (NCIM 5463) - Sacheti, Poonam; Bhonsle, Hemangi S.; Patil, Rajendra; Kulkarni, Mahesh J.; Srikanth, Rapole; Gade, Wasudeo N. (RSC Advances, 2013)
In the present study, arsenate [As(V)] tolerant organisms were isolated from a metal contaminated site, and identified by 16S rDNA sequencing as Exiguobacterium sp. Arsenomics (omics of arsenic response) in Exiguobacterium sp. PS via two-dimensional gel electrophoresis (2-DGE) coupled with identification of proteins using MALDI-TOF MS, MALDI-TOF MS/MS and LC/MSE are studied vide this paper. Out of 2460 Coomassie stained proteins, 270 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 45 spots (proteins) were subjected to MALDI-TOF MS/MS, MALDI-TOF/TOF and LC/MSE. Out of these, 33 were identified and categorized into several functional categories (including both known and novel/putative stress responsive proteins) viz., carbohydrate and energy metabolism, stress response, motility, amino acid, and purine and protein synthesis. The identifications of unique proteins, phosphate ABC transporter ATPase subunit and pyridine nucleotide disulfide oxidoreductase, are the significant findings of the present study which may be used as markers of As(V) stress in Exiguobacterium sp. PS. The absence of As(V) reductase activity and non-amplification of the arsC gene of the ars operon suggests that the classical mechanism of As(V) resistance may not be operating in Exiguobacterium sp. PS. Lastly, considering the fact that proteomic studies under As(V) stress were performed only in Gram negative organisms, this study is the first comprehensive endeavour to explore the mechanism of As(V) response in Gram positive organisms, Exiguobacterium sp. PS at the proteomic level.

Xylitol production by cyberlindnera (Williopsis) saturnus, a tropical mangrove yeast from xylose and corn cob hydrolysate - Kamat, S.; Gaikwad, S.; Kumar, A. Ravi; Gade, Wasudeo N. (Journal of Applied Microbiology, 2013)
AimPotential for xylitol production from xylose and corn cob hydrolysate by a tropical mangrove yeast. Methods and ResultsIn the present study, 21 fungi were isolated from detritus-based mangrove wetlands along the Indian west coast. Of these, one yeast isolate had the ability to grow and assimilate xylose producing significant amounts of xylitol (3863gl(-1)). A maximum yield of 054gg(-1) was obtained after 144h of growth on xylose (150gl(-1)) and corn cob hydrolysate (CCH, containing 65gl(-1) xylose). Using biochemical and molecular methods, the yeast was identified as Cyberlindnera (Williopsis) saturnus. Preliminary characterization of enzymes in the cell-free extract revealed that while xylose reductase (XR) preferred NADPH to NADH as cofactor, xylitol dehydrogenase (XDH) was NAD specific. ConclusionsSignificant amounts of xylitol could be produced on CCH using C.saturnus isolated from tropical mangrove wetlands. The yeast has the potential to assimilate rather than ferment xylose as its XR has a preference for NADPH. Significance and Impact of the StudyMicrobes offer an economically viable and green approach for production of xylitol, an industrially important compound. A mangrove ecosystem with its battery of lignocellulolytic enzymes is an ideal location for isolating fungi capable of producing xylitol from agroindustrial waste such as CCH.
Keywords: corn cob hydrolysate; Cyberlindnera; mangrove; Williopsis; xylitol; Xylose; Yeast

Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Functional characterization and transient expression manipulation of a new sesquiterpene synthase involved in beta-caryophyllene accumulation in Ocimum - Jayaramaiah, Ramesha H.; Anand, Atul; Beedkar, Supriya D.; Dholakia, Shushan B.; Punekar, Sachin A.; Kalunke, Raviraj M.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochemical And Biophysical Research Communications, 2016)
The genus Ocimum has a unique blend of diverse secondary metabolites, with major proportion of terpenoids including mono- and sesquiterpenes. Although, beta-Caryophyllene, bicyclic sesquiterpene, is one of the major terpene found in Ocimum species and known to possess several biological activities, not much is known about its biosynthesis in Ocimum. Here, we describe isolation and characterization of beta-caryophyllene synthase gene from Ocimum kilimandscharicum Gurke (OkBCS- GenBank accession no. KP226502). The open reading frame of 1629 bp encoded a protein of 542 amino acids with molecular mass of 63.6 kDa and pl value of 5.66. The deduced amino acid sequence revealed 50-70% similarity with known sesquiterpene synthases from angiosperms. Recombinant OkBCS converted farnesyl diphosphate to beta-caryophyllene as a major product (94%) and 6% alpha-humulene. Expression variation of OkBCS well corroborated with beta-caryophyllene levels in different tissues from five Ocimum species. OkBCS transcript revealed higher expression in leaves and flowers. Further, agro-infiltration based transient expression manipulation with OkBCS over-expression and silencing confirmed its role in beta-caryophyllene biosynthesis. These findings may potentially be further utilized to improve plant defense against insect pests. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: beta-Caryophyllene; Natural product biosynthesis; Ocimum; Terpene synthase; Transient expression

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome